Kinerja Pelayanan Administrasi Kependudukan - Agustina, Ika (Jurnal Administrasi Publik, 2013)
Abstract: Civil Registration Service Performance. The research was conducted on the basis of the criticism against the administration that service performance is still lacking, including the lack of timeliness, number of requirements, and procedures convoluted. This makes people lazy to take care of population administration as family cards and birth certificates. The purpose of this study was to determine and describe the process of population administration services in the manufacture of family cards and birth certificates at the Department of Population and Civil Registration Jombang. This type of research is a qualitative researcher.The results of this study indicate that the performance of administrative services at the residence of Population and Civil Registration Agency Jombang seen from the aspect of the ability to complete the task is either because employees already have a good level of education, being able to do the work on time, and discipline. Service mechanism is applying the principle of simplicity. Key Words: Performance, Services, Civil Registration Abstrak: Kinerja Pelayanan Administrasi Kependudukan . Penelitian ini dilakukan atas dasar adanya kritikan terhadap kinerja pelayanan administrasi kependudukan yang masih kurang, meliputi kurangnya ketepatan waktu, banyaknya persyaratan, dan prosedur yang berbelit-belit. Hal ini membuat masyarakat menjadi malas untuk mengurus administrasi kependudukan seperti Kartu keluarga dan Akta Kelahiran. Tujuan penelitian ini adalah untuk mengetahui dan memaparkan proses pelayanan administrasi kependudukan dalam pembuatan kartu keluarga dan akta kelahiran pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jombang.Jenis penelitian yang digunakan peneliti adalah kualitatif. Hasil dari penelitian ini menunjukkan bahwa kinerja pelayanan administrasi kependudukan pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jombang dilihat dari aspek kemampuan dalam menyelesaikan tugas sudah baik karena pegawai sudah memiliki tingkat pendidikan yang baik, mampu mengerjakan tugas tepat waktu, dan disiplin. Mekanisme pelayanan sudah menerapkan prinsip Kesederhanaan. Kata Kunci: Kinerja, Pelayanan, Administrasi Kependudukan